Ceramic Innovation: Designing Souvenirs to Enhance Local Cultural Identity (Al-Academy, 2025)
This research explores ceramic innovation and its role in designing souvenirs that enhance national cultural identity by integrating traditional elements with modern design. Six ceramic product groups, including incense burners, vases, and decorative plates, were developed incorporating authentic cultural symbols such as Qat Asiri motifs and Arabic calligraphy. Data were collected through evaluations by 23 specialized experts using a questionnaire that measured aesthetics, innovation, cultural symbolism, functionality, and market competitiveness. The results indicate strong acceptance of designs that successfully blend tradition with modernity, particularly excelling in innovation and cultural symbolism. The study concludes that enhancing the integration of heritage with contemporary design significantly strengthens national cultural identity and contributes to the development of competitive products both locally and globally. The research recommends further studies and the development of marketing strategies to maximize the impact of these innovative ceramic designs.